Official rotation and corporate innovation: Evidence from the governor rotation - Xiangyan Shi; Bu Danlu; Chenyu Zhang (China Journal of Accounting Research, 2020)
Rotation is a practice whereby officials are regularly moved between equally ranked positions. Focusing on governor rotation, this paper examines the effect of official rotation on corporate innovation in China. First, we find that official rotation significantly promotes corporate innovation, including enterprises' innovation investment, quantity, and quality. Second, we find that the effect of official rotation on corporate innovation varies because of official and regional heterogeneity. Officials rotating from other provinces significantly stimulate corporate innovation, but officials rotating from the central government have an insignificant influence on corporate innovation. In addition, officials rotating to non-eastern regions significantly enhance corporate innovation, while officials rotating to eastern regions have a negligible impact on corporate innovation. We further examine the driving mechanism behind the effect of official rotation on corporate innovation and find that officials rotating from eastern regions to non-eastern regions can significantly promote corporate innovation, but officials rotating from non-eastern regions to eastern regions do not boost corporate innovation. These findings imply that the different effects of official rotation on corporate innovation are due to the official experience effect. We also find that official rotation can promote corporate innovation through reducing corporate charitable donations and increasing corporate innovation subsidies. In a supplementary analysis, we find that GDP-oriented performance appraisal pressure weakens the effect of official rotation on corporate innovation. The lower the pressure on officials regarding their performance, the more significant the effect of official rotation on corporate innovation. In addition, official rotation can significantly promote the development of the regional economy and improve the GDP growth rate via corporate innovation, which is a micro-level economic growth effect of official rotation. Overall, our findings further verify the economic effect of official rotation and extend our understanding of the influencing factors of corporate innovation from the perspective of the official governance system. Our findings also have clear policy implications for how the government can improve the official governance model to promote corporate innovation during the transition period of the national innovation system.
Keywords: 650; Official rotation; Corporate innovation; Official heterogeneity; Region heterogeneity